Dual mobility acetabular construct with freedom constrained liner for treatment of recurrent dislocations after total hip arthroplasty: A case report and literature review. (2020) - Onochi, Yuuki; Fukui, Kiyokazu; Kaneuji, Ayumi; Ichiseki, Toru; Wang, Xipeng; Kawahara, Norio
Highlights: Dual-mobility bearings improve stability in total hip arthroplasty (THA) but may fail to prevent postoperative dislocation. Dry revision with a compatible constrained liner system can provide an effective salvage option for instability after THA. The unique G7 constrained liner system offers good short-term stability and range of motion. Abstract: Introduction: Recurrent dislocation after total hip arthroplasty (THA) using the dual mobility cup system can present challenges, while dual-mobility THA bearings can improve stability in both primary and revision total hip arthroplasties. Presentation of case: A 72-year-old woman with a history of schizophrenia underwent a left primary THA using the G7 dual mobility system. Two postoperative posterior dislocations occurred within 2 months post-surgery. The patient underwent revision surgery in which the metal liner and dual mobility head were exchanged using the Freedom constrained liner system without revision of the cup and stem. As of this writing, 28 months after the revision surgery, no further dislocations have occurred. The implants are stable, and the patient has good range of motion. Discussion: Dual-mobility bearings are utilized to improve stability in both primary and revision total hip arthroplasties, but even if the dual mobility system is chosen, it sometimes fails to prevent postoperative dislocation. Although a relatively high failure rate has been reported in THA using the constrained liner system, this patient's clinical course suggests that the G7 Freedom constrained liner system can be an efficacious option for some patients with unstable hip joints who undergo THA using the dual mobility system. Conclusion: A modern constrained liner system such as the G7 Freedom liner may provide an improved salvage solution for joint instability in dual mobility THA.